2004
DOI: 10.1158/0008-5472.can-04-1525
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal Irradiation of Human Tumor Cells Modulates Phenotype Resulting in Enhanced Killing by Cytotoxic T Lymphocytes

Abstract: ABSTRACT؉ CTLs compared with nonirradiated counterparts. We then used microarray analysis to broaden the scope of observed changes in gene expression after radiation and found that many additional genes had been modulated. These up-regulated gene products may additionally enhance the tumor cells' susceptibility to T-cell-mediated immune attack or serve as additional targets for immunotherapy. Overall, the results of this study suggest that nonlethal doses of radiation can be used to make human tumors more amen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
401
1
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 484 publications
(432 citation statements)
references
References 36 publications
15
401
1
4
Order By: Relevance
“…23 In addition to confirming some of these findings in this study using TRAMP-C1 cells, we further found that IL-3-induced Fas antigen expression, as did RT. The effect of RT is similar to recent findings by Chakraborty et al [5][6][7] They have proposed that radiationinduced tumor phenotype changes could enhance tumor cell susceptibility to antigen-specific CTL-mediated killing. The mechanism that mediates this type of phenotypic switch by IL-3 is still unclear.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…23 In addition to confirming some of these findings in this study using TRAMP-C1 cells, we further found that IL-3-induced Fas antigen expression, as did RT. The effect of RT is similar to recent findings by Chakraborty et al [5][6][7] They have proposed that radiationinduced tumor phenotype changes could enhance tumor cell susceptibility to antigen-specific CTL-mediated killing. The mechanism that mediates this type of phenotypic switch by IL-3 is still unclear.…”
Section: Discussionsupporting
confidence: 88%
“…As radiation-induced changes in MHC class I, ICAM-1, and Fas expression by tumor cells irradiated in vitro also have been reported [5][6][7] we examined expression of these molecules on TRAMP-C1 cells with and without Doxregulated IL-3 expression 4 h following a single in vitro dose of 0 or 7 Gy. Radiation was given 24 h after Dox treatment.…”
Section: The Influence Of Il-3 Gene Transfer and Radiation On Tumor Pmentioning
confidence: 92%
See 1 more Smart Citation
“…Further preclinical studies showed similar findings with human cell lines [9]. Twenty-three human carcinoma cell lines (12 colon, 7 lung, 4 prostate) were subjected to 10 Gy of radiation.…”
Section: Vaccine and Radiationmentioning
confidence: 54%
“…Radiotherapy may also contribute to enhance killing activity of immune cells since irradiation mediates many effects on cells and tissues that may stimulate an immune response [30]. For example, low doses of ionising irradiation upregulate expression of MHC class I molecules [31] and tumourassociated antigens [32], as well as adhesion molecules by endothelial cells [33], thereby boosting cytotoxic T-cell activity [34].…”
Section: Discussionmentioning
confidence: 99%